2014
DOI: 10.1093/infdis/jiu551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment Interruption Patterns on Treatment Success Among Patients With Multidrug-Resistant Tuberculosis in Armenia and Abkhazia

Abstract: This study shows that in a directly observed therapy-based MDR tuberculosis program, treatment interruptions at short intervals of ≥3 days directly affect treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 19 publications
3
42
2
2
Order By: Relevance
“…The pooled estimate of the MDR-TB prevalence in Iran is higher than that in Iraq, Turkey, and Pakistan. Additionally, the prevalence in Iran (27%, 95% CI 16-39) was higher than that of the overall point estimate for all of the studies included (16%, 95% CI [11][12][13][14][15][16][17][18][19][20]. The higher prevalence of MDR-TB in Iran when compared to the other countries in the region might be explained by the fact that Iran has a greater capacity to detect resistant bacilli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled estimate of the MDR-TB prevalence in Iran is higher than that in Iraq, Turkey, and Pakistan. Additionally, the prevalence in Iran (27%, 95% CI 16-39) was higher than that of the overall point estimate for all of the studies included (16%, 95% CI [11][12][13][14][15][16][17][18][19][20]. The higher prevalence of MDR-TB in Iran when compared to the other countries in the region might be explained by the fact that Iran has a greater capacity to detect resistant bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects associated with MDR-TB treatment are barriers leading to lack of adherence to treatment. Bastard et al 15 reported that poor adherence to treatment due to intolerance of the adverse effects was one of the predictors of unsuccessful treatment outcomes. Moreover, Sanchez-Padilla et al 24 reported that the main reason for discontinuing treatment in all the patients who were interviewed was difficulty in dealing with side effects.…”
Section: Care For Mdr-tb Patientsmentioning
confidence: 99%
“…Despite the acceptable overall lost to follow-up rate below 10% of HIV-positive DR-TB patients, there was a higher proportion of patients who interrupted treatment in the first 3 months among patients not on ART. Adherence is a wellknown strong factor associated with DR-TB and HIV treatment success, and a lower adherence predict unsuccessful outcome [26,33,34]. Surprisingly, the profile of resistance at treatment start was not associated with DR-TB treatment outcomes among HIV-positive patients, while MDR-TB patients are expected to have worse outcomes than other DR-TB patients [21].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian oleh Bastard (2015) menghasilkan lama penundaan e" 3 hari berisiko 3,87 (95% CI, 1,66-8,98) kali lebih besar mengalami kegagalan pengobatan. 21 Kirana (2018) mengkategorikan interval inisiasi pengobatan > 30 hari berisik o 1,11 (95% CI, 1,00-1,24) lebih besar mendapatkan hasil pengobatan buruk (tidak sembuh). 4 Beberapa penelitian lain membuat kategori yang berbeda-berbeda terkait dengan penundaan pengobatan yang berisiko terhadap hasil pengobatan.…”
Section: Factors Associated With Recovery Success After Short Treatmeunclassified